A new ImageJ plug-in "actogramJ" for chronobiological analyses - Schmid, Benjamin; Helfrich-Foerster, Charlotte; Yoshii, Taishi (Journal of Biological Rhythms, 2011)
While the rapid development of personal computers and high-throughput recording systems for circadian rhythms allow chronobiologists to produce huge amounts of data, the software to analyze them often lags behind. Here, we announce newly developed chronobiology software that is easy to use, compatible with many different systems, and freely available. Our system can perform the most frequently used analyses: actogram drawing, periodogram analysis, and waveform analysis. The software is distributed as a pure Java plug-in for ImageJ and so works on the 3 main operating systems: Linux, Macintosh, and Windows. We believe that this free software raises the speed of data analyses and makes studying chronobiology accessible to newcomers. © 2011 SAGE Publications.
Created from Fastlane, Scopus look-up
Keywords: Ξ2 periodogram; actogram; chronobiological data; circadian rhythm; free software; ImageJ; Lomb-Scargle periodogram